Daytime Exposure to Blue-Enriched Light Counters the Effects of Sleep Restriction on Cortisol, Testosterone, Alpha-Amylase and Executive Processes - Faraut, Brice; Andrillon, Thomas; Drogou, Catherine; Gauriau, Caroline; Dubois, Alexandre; Servonnet, Aurélie; Van Beers, Pascal; Guillard, Mathias; Gomez-Merino, Danielle; Sauvet, Fabien; Chennaoui, Mounir; Léger, Damien (Frontiers in Neuroscience, 2020)
Sleep debt is becoming a better acknowledged cause of physiological stress and neurobehavioral deficits with major public-health concerns. We investigated whether exposure to blue light during daytime could be an efficient countermeasure to limit sleep restriction’s impact on relevant behavioral (stress, sleepiness, sustained attention, and memory performance) and physiological (saliva cortisol, testosterone, and alpha-amylase) markers. Our semi-ecological, crossover, randomized design included 17 young men that underwent two sleep-restricted nights (3 h each) followed or not by blue light exposure (30-min-long sessions at 100 lux repeated four times throughout the day). Behavioral and physiological measurements were performed in the lab but outside these periods the participants kept following their usual routine. After sleep restriction, morning cortisol and testosterone, and afternoon alpha-amylase levels decreased. In parallel, subjective ratings of stress and sleepiness increased while performance on the sustained attention and memory tasks deteriorated. In contrast, after periods of blue light exposure, all these parameters were largely restored to baseline levels, despite an identical sleep restriction procedure, although this restorative effect was reduced for the memory task. Our findings suggest that even short exposure to blue light could trigger persistent beneficial effects throughout the day and could be potentially efficient in real-life settings.